Long-term follow-up of cystinosis patients treated with 0.55% cysteamine hydrochloride. Issue 5 (27th June 2020) - Liang, Hong; Labbé, Antoine; Baudouin, Christophe; Plisson, Celine; Giordano, Vincenzo
Abstract : Background/Aims: Cystinosis is a rare, autosomal recessive disorder causing defective transport of cystine out of lysosomes. Cystadrops (0.55% cysteamine hydrochloride in viscous solution) has been used on a named-patient basis to treat the accumulation of cystine crystals in the cornea in patients with cystinosis. Methods: Retrospective analysis of the Temporary Authorisation for Use cohort of 130 patients who received Cystadrops between 2013 and 2017 in France. Results: Patients received an average dosage of 3.3 (±0.94) instillations per eye per day. Over the duration of follow-up, of up to 45 months, patients maintained visual acuity scores of 0.0, which approximated normal. Corneal cystine crystal scores tended to decrease over time, stabilising after around 27 months between 1.22 and 1.87. Photophobia decreased within 3 months, stabilising on scores of around 1.5 and 1.7. 47 non-serious adverse reactions were reported, which were generally transient irritation, stinging or blurred vision. Four serious adverse events were reported, including keratitis and corneal ulcer, but these may have been caused by the underlying disease. Conclusion: This large safety cohort confirms the efficacy, safety and tolerability of Cystadrops in real-world clinical practice.